2002
DOI: 10.1021/ic025637t
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electrospray Mass Spectrometry (ESI-MS) for the Study of Europium(III) Complexation with Bis(dialkyltriazinyl)pyridines and Its Implications in the Design of New Extracting Agents

Abstract: ESI mass spectrometry was used to investigate the europium complexation by tridentate ligands L identical with 2,6-bis(5,6-dialkyl-1,2,4-triazin-3-yl)-pyridines (DATP) that have shown unique separation properties of actinides(III) from lanthanides(III) in nitric acid solutions. Complexes of three ligands, namely methyl (DMTP), n-propyl (DnPTP), and iso-propyl (DiPTP), have been investigated in acidic solutions to check the aqueous-phase stability of Eu(L)(3)(3+) ions identified previously in the solid state. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 50 publications
15
101
1
Order By: Relevance
“…Several authors considered the ion response factors to be roughly equivalent for all the species in solution (Wang & Gokel, 1996;Goolsby et al, 1999;Reany et al, 2000;Ross, Ikonomou, & Orians, 2000a;Moulin et al, 2001;Colette et al, 2002;Jacopin et al, 2003) or for part of them (Cheng et al, 1992). (g) Finally, high concentrations of supporting electrolyte cannot be used in ESI-MS, because the signal of the analyte ions would be suppressed in the presence of high concentrations of other electrolytes (Smith et al, 1993;.…”
Section: Other Problemsmentioning
confidence: 99%
“…Several authors considered the ion response factors to be roughly equivalent for all the species in solution (Wang & Gokel, 1996;Goolsby et al, 1999;Reany et al, 2000;Ross, Ikonomou, & Orians, 2000a;Moulin et al, 2001;Colette et al, 2002;Jacopin et al, 2003) or for part of them (Cheng et al, 1992). (g) Finally, high concentrations of supporting electrolyte cannot be used in ESI-MS, because the signal of the analyte ions would be suppressed in the presence of high concentrations of other electrolytes (Smith et al, 1993;.…”
Section: Other Problemsmentioning
confidence: 99%
“…It was shown that BTPs act as tridentate ligands, [10] forming 1:3 complexes with An III and Ln III in the solid state [10][11][12] and in organic solution. [6,[13][14][15][16][17][18][19]36,37] Titrations in organic phase [16,17] [16,17,19] We perform a comparative study on the complexation of Cm III and Eu III with nPr-BTP [2,6-bis(5,6-dipropyl-1,2,4-triazin-3-yl)pyridine] ( Figure 1) in water/methanol, 1:1. The formation of the respective BTP complexes is followed by time resolved laser-induced fluorescence spectroscopy (TRLFS).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3a [11,12]. In this particular case (DiPTP) and surprisingly enough only 1-3 complex are observed.…”
Section: -Hydroxyethane-11 -Diphosphonic Acid (Hedp) -Uranium(vi)mentioning
confidence: 56%